Desain Sistem Kontrol Cerdas Penyeimbangan Sel Baterai yang disusun Seri - Safitri, Wiwit Yuni; Rahmawati, Asde; Fahrizal, Fahrizal; Akramunnas, Basthul Wajhi; Septiyeni, Tesya Uldira (SURYA TEKNIKA, 2026)
Batteries are used as energy storage devices due to their high energy and power density. Battery cells are typically connected in series to achieve higher voltage and power capacity. However, differences in chemical and electrical characteristics of each cell can lead to voltage imbalance after repeated charge-discharge cycles. This condition ultimately reduces the total capacity of lithium-ion batteries and shortens their lifespan. This study introduces an efficient and high-performance cell balancing mechanism specifically designed for series-connected batteries. To optimize the balancing process and ensure voltage uniformity across the cells, an intelligent Fuzzy Logic Kontroler is integrated to control the balancing circuit. Simulation results show that the use of intelligent control can achieve battery voltage balance within 60 seconds.